Mutations in Plasmodium falciparum dihydrofolate reductase and dihydropteroate synthase of isolates from the Amazon Region of Brazil - KF Vasconcelos; CV Plowe; CJ Fontes; D Kyle; DF Wirth; LH Pereira da Silva; MG Zalis (Memorias do Instituto Oswaldo Cruz, 2000)
Since the late 1970s pyrimethamine-sulfadoxine (PS; FansidarTM Hoffman-LaRoche, Basel) has been used as first line therapy for uncomplicated malaria in the Amazon basin. Unfortunately, resistance has developed over the last ten years in many regions of the Amazon and PS is no longer recommended for use in Brazil. In vitro resistance to pyrimethamine and cycloguanil (the active metabolite of proguanil) is caused by specific point mutations in Plasmodium falciparum dihydrofolate reductase (DHFR), and in vitro resistance to sulfadoxine has been associated with mutations in dihydropteroate synthase (DHPS). In association with a proguanil-sulfamethoxazole clinical trial in Brazil, we performed a nested mutation-specific polymerase chain reaction to measure the prevalence of DHFR mutations at codons 50, 51, 59, 108 and 164 and DHPS mutations at codons 436, 437, 540, 581 and 613 at three sites in the Brazilian Amazon. Samples from two isolated towns showed a high degree of homogeneity, with the DHFR Arg-50/Ile-51/Asn-108 and DHPS Gly-437/Glu-540/Gly-581 mutant genotype accounting for all infections in Peixoto de Azevedo (n = 15) and 60% of infections in Apiacás (n = 10), State of Mato Grosso. The remaining infections in Apiacás differed from this predominant genotype only by the addition of the Bolivia repeat at codon 30 and the Leu-164 mutation in DHFR. By contrast, 17 samples from Porto Velho, capital city of the State of Rondônia, with much in- and out-migration, showed a wide variety of DHFR and DHPS genotypes.